Does Economic Motivation Determine the Continuance of Social Media Use? A Technology Continuance Theory Perspective: A Case of Facebook - Fidelia Serli Korey; Dedi Iskandar Inan; Ratna Juita; Muhamad Indra (JUSIFO : Jurnal Sistem Informasi, 2025)
This study investigates whether economic motivation—specifically through the Facebook Reels monetization feature “Stars”—significantly influences users’ continued engagement with the platform. Drawing on Technology Continuance Theory (TCT), this research integrates financial and social drivers including remuneration motive, recognition, and reciprocal benefits to examine their effects on attitude, continuance usage intention, and word-of-mouth (WoM) behavior. Data were collected from 174 active Facebook Reels users in Manokwari, Indonesia, and analyzed using partial least squares structural equation modeling (PLS-SEM). Results reveal that network exposure significantly enhances remuneration motive, recognition, and reciprocal benefits. However, only reciprocal benefits positively influence user attitude, which in turn predicts both continued usage and WoM intention. The model’s relatively low R-square values suggest that future research should consider broader psychological and platform-related variables. These findings underscore the need for a holistic approach in designing monetization systems that balance economic rewards with social engagement to ensure sustainable user retention.